Komunikasi Antar Pribadi Anak dengan Orang Tua Beda Agama di Denpasar - Praasada, Ni Nyoman Cita; Suryawati, I Gusti Agung Alit; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2019)
ABSTRACT Through interpersonal communication, communicants can interact with others, and express themselves to others. In families, there are often differences of opinion or different ways of communicating between parents and children, and similarly with children who have parents of different religions. The purpose . of this study . aims t o . find . out how to form . interpersonal communication between children with interfaith parents in Denpasar City. The analytical technique used in the study through several stages, namely the calculation of the average analysis techniques and conclusions. The . results . showed . that even though . there . were differences in . age and religion with their parents, it did not prevent children from their parents from being able to have an attitude of openness, empathy, freedom of expressing ideas between children and parents with different beliefs.   Keywords: Communication Pattern, Interpersonal Communication, Religion